2016
DOI: 10.2134/cftm2016.0002
|View full text |Cite
|
Sign up to set email alerts
|

Corn Response to Row Spacing and Seeding Rate Varies by Hybrid and Environment in Kentucky

Abstract: There has been recent interest in growing corn in narrow rows (<30 inches wide) and at dense plant populations to increase grain yields. The purpose of this study was to evaluate three corn hybrids adapted to the midsouthern United States at multiple row spacings and seeding rates. Studies were established

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Narrow row spacing, pooled over site-year and plant population, increased stalk diameter by 4% (p = .0009; Table plant population, pooled over site-year and row spacing, decreased in a negative quadratic trend as plant population increased (p < .0001; Table 4 & 5). Similar studies reported that increasing plant population reduced stalk diameter (Bernhard & Below, 2020;Stinson & Moss, 1960;Tetio-Kagho & Gardner, 1988;Mackey et al 2016).…”
Section: Mid-season Morphologysupporting
confidence: 52%
See 1 more Smart Citation
“…Narrow row spacing, pooled over site-year and plant population, increased stalk diameter by 4% (p = .0009; Table plant population, pooled over site-year and row spacing, decreased in a negative quadratic trend as plant population increased (p < .0001; Table 4 & 5). Similar studies reported that increasing plant population reduced stalk diameter (Bernhard & Below, 2020;Stinson & Moss, 1960;Tetio-Kagho & Gardner, 1988;Mackey et al 2016).…”
Section: Mid-season Morphologysupporting
confidence: 52%
“…The other four site-years that did not experience root lodging and maximized grain yield at 114,386 to 119,125 plants ha -1 (Table 4 & 6; Figure 2). Granted, hybrids may have a unique response to plant population (Brown et al, 1970;Bruns & Abbas, 2006;Mackey et al, 2016;Widdicombe & Thelen, 2002), even through the use of conservative plateau regression models, our results indicate slightly greater AOPP's than the literature (Boomsma et al, 2009;Bruns et al, 2012;Farnham, 2001;Van Roekel & Coulter, 2012;Widdicombe & Thelen, 2002). Assefa et al, (2016) conducted a meta-analysis and suggested that not all environments require similar plant populations.…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 62%
“…However, there are inconsistent results regarding the yield advantage of narrow rows (<30‐inch) over the wider (≥30‐inch) rows. Although several studies show a 2.7 to 10% yield increase by planting corn in narrow rows (Barbieri et al, 2000; Johnson and Hoverstad, 2002; Widdicombe and Thelen, 2002; Shapiro and Wortmann, 2006; Thelen, 2006; Williams et al, 2014: Nelson et al, 2015), some studies show either yield reduction or no yield advantage for narrow rows (Farnham, 2001; Lee, 2006; Robles et al, 2012; Van Roekel and Coulter, 2012; Novacek et al, 2013; Mackey et al, 2016). The most consistent yield advantage (7 to 10%) of narrow rows over wider rows has been documented in the north‐central USA (Porter et al, 1997; Johnson and Hoverstad, 2002; Widdicombe and Thelen, 2002; Sharratt and McWilliams, 2005; Thelen, 2006).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Mackey et al. (2016) concluded thorough selection of commercial hybrids along with management practices such as plant populations suitable for different growing environments may prove to have greater impact with improving yields compared to the selection of a row spacing.…”
Section: Introductionmentioning
confidence: 99%
“…While evaluating corn, Van Roekel and Coulter (2012) concluded no physiological or yield advantages were observed when transitioning from a 30 inch to a 20-inch row spacing in southern Minnesota. Mackey et al (2016) concluded thorough selection of commercial hybrids along with management practices such as plant populations suitable for different growing environments may prove to have greater impact with improving yields compared to the selection of a row spacing.…”
mentioning
confidence: 99%